Vic Midgley Writes Home: A Letter from New Zealand, 1939 - Mouat, Jeremy (Labour / Le Travail, 1992)
Introduces and provides background on the letter written on Feb. 21, 1939, from Victor Midgley in New Zealand to his friend and fellow socialist, Angus MacInnis, in Vancouver. Midgley, who was formerly a prominent member of the BC labour movement and the CCF, gives his assessment of union and political affairs in New Zealand, where a Labour government was then in power. The opening page of the handwritten letter is reproduced.
Keywords: History; LABOUR/LE Travail (Book); Labor movement; Letters; MACINNIS; Angus; MIDGLEY; Victor; NEW Zealand; Politics & government; WORLD politics